PENYULUHAN PENCEGAHAN HIPERURISEMIA PADA JAMAAH MASJID IHSAN DARUSSALAM, AIA PACAH KOTA PADANG - Suharni Suharni; Rosmaini Rosmaini; Erdanella Setiawati; Letvi Mona; Yanti Fitri Yasa; Muhammad Rizki Saputra (Nusantara Hasana Journal, 2026)
Hyperuricemia is a condition characterized by elevated serum uric acid levels, which serves as a primary risk factor for gout and is closely associated with cardiometabolic and renal disorders. Lifestyle factors, such as high-purine diets, obesity, alcohol consumption, physical inactivity, and a lack of routine health screenings, contribute significantly to the high incidence of hyperuricemia. This activity aimed to enhance the knowledge of the congregants at the Ihsan Darussalam Mosque, Aia Pacah, Padang City, regarding hyperuricemia prevention through community-based health counseling. The method employed was health counseling consisting of lectures and interactive discussions utilizing leaflets, complemented by personalized education for the participants. The results demonstrated an improvement in the participants' understanding of the definition of hyperuricemia, its risk factors, high-purine foods, as well as the importance of a healthy diet, physical activity, and routine health screenings. Community-based health counseling within a mosque environment has the potential to foster behavioral changes among congregants toward adopting a healthy lifestyle to prevent hyperuricemia and its complications.